A Novel Eight Octapeptide Repeat Insertion in PRNP Causing Prion Disease in a Danish Family. Issue 7 (22nd April 2019) - Areškevičiūtė, Aušrinė; Høgh, Peter; Bartoletti-Stella, Anna; Melchior, Linea Cecilie; Nielsen, Pia Rude; Parchi, Piero; Capellari, Sabina; Broholm, Helle; Scheie, David; Lund, Eva Løbner
Abstract: Octapeptide repeat insertions (OPRI) found in the prion protein gene ( PRNP ) constitute a subgroup of pathogenic mutations linked to inherited prion diseases, a hallmark of which is a misfolded prion protein. The number of repeats in OPRI has been associated with different disease phenotypes. However, due to the rarity of the cases and heterogenous disease manifestations, the recognition and classification of these variants has been difficult. Here, we report the first Danish family, the fifth worldwide, carrying a novel 8-OPRI with a unique sequence of the additional 8 inserts: R1-R2-R2-R3- R2-R2-R2a-R2-R3g-R2-R2-R3 -R4. The mutation was found on the allele coding for methionine at codon 129 in the PRNP gene. The clinical exome sequencing revealed that no other dementia-associated genes harbored pathogenic alterations. Mutation carriers had onset of symptoms in their early thirties, but disease duration varied from 5 to 11 years. Progressive dementia with psychiatric and motor symptoms were the most prominent clinical features. Clinical, pathological, and genetic characteristics of other 4 reported families with 8-OPRI were reviewed and compared with the findings in the Danish family.